Cancel Culture and Contemporary Film Criticism or is the Voice of Film Critics Cancelled, Too? - Szabó, Helga (AMERICANA E-journal of American Studies in Hungary, 2022)
Cancel Culture and Contemporary Film Criticism or is the Voice of Film Critics Cancelled, Too?